3‐Sulfinopropionyl‐coenzyme A (3SP‐CoA) desulfinase from Advenella mimigardefordensis DPN7T: crystal structure and function of a desulfinase with an acyl‐CoA dehydrogenase fold. (1st June 2015) - Schürmann, Marc; Meijers, Rob; Schneider, Thomas R.; Steinbüchel, Alexander; Cianci, Michele
<x xml:space="preserve">Abstract</x> 3‐Sulfinopropionyl‐coenzyme A (3SP‐CoA) desulfinase (AcdDPN7; EC 3.13.1.4) was identified during investigation of the 3, 3′‐dithiodipropionic acid (DTDP) catabolic pathway in the betaproteobacterium Advenella mimigardefordensis strain DPN7T. DTDP is an organic disulfide and a precursor for the synthesis of polythioesters (PTEs) in bacteria, and is of interest for biotechnological PTE production. AcdDPN7 catalyzes sulfur abstraction from 3SP‐CoA, a key step during the catabolism of DTDP. Here, the crystal structures of apo AcdDPN7 at 1.89 Å resolution and of its complex with the CoA moiety from the substrate analogue succinyl‐CoA at 2.30 Å resolution are presented. The apo structure shows that AcdDPN7 belongs to the acyl‐CoA dehydrogenase superfamily fold and that it is a tetramer, with each subunit containing one flavin adenine dinucleotide (FAD) molecule. The enzyme does not show any dehydrogenase activity. Dehydrogenase activity would require a catalytic base (Glu or Asp residue) at either position 246 or position 366, where a glutamine and a glycine are instead found, respectively, in this desulfinase. The positioning of CoA in the crystal complex enabled the modelling of a substrate complex containing 3SP‐CoA. This indicates that Arg84 is a key residue in the desulfination reaction. An Arg84Lys mutant showed a complete loss of enzymatic activity, suggesting that the guanidinium group of the arginine is essential for desulfination. AcdDPN7 is the first desulfinase with an acyl‐CoA dehydrogenase fold to be reported, which underlines the versatility of this enzyme scaffold.